Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1183/13993003.01153-2017
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory adverse effects of opioids for breathlessness: a systematic review and meta-analysis

Abstract: Previous studies have shown that opioids can reduce chronic breathlessness in advanced disease. However, physicians remain reluctant to prescribe opioids for these patients, commonly due to fear of respiratory adverse effects. The aim of this study was to systematically review reported respiratory adverse effects of opioids in patients with advanced disease and chronic breathlessness.PubMed, Embase, the Cochrane Central Register of Controlled Trials, CINAHL, ClinicalTrials.gov and the reference lists of releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 83 publications
7
54
0
7
Order By: Relevance
“…17,18 The reports of (mainly mild) constipation, nausea, and vomiting in the morphine group are similar to other published reports of low dose morphine for breathlessness 14,15,38,39 but are nonetheless important. We found no respiratory depression consistent with a recent systematic review and meta-analysis.…”
Section: What This Study Addssupporting
confidence: 83%
See 3 more Smart Citations
“…17,18 The reports of (mainly mild) constipation, nausea, and vomiting in the morphine group are similar to other published reports of low dose morphine for breathlessness 14,15,38,39 but are nonetheless important. We found no respiratory depression consistent with a recent systematic review and meta-analysis.…”
Section: What This Study Addssupporting
confidence: 83%
“…17,18 The reports of (mainly mild) constipation, nausea, and vomiting in the morphine group are similar to other published reports of low dose morphine for breathlessness 14,15,38,39 but are nonetheless important. 17 In the morphine group, all breathlessness measures, apart from week 4 average breathlessness, had greater improvement from baseline than the placebo group. It is possible that patients with heart failure and renal dysfunction may be susceptible to nausea as blood brain barrier permeability is increased, at least in acute kidney injury, 40 and initial co-prescription might be useful.…”
Section: What This Study Addssupporting
confidence: 83%
See 2 more Smart Citations
“…Ekström and colleagues71 confirmed that short-term use of opioids are associated with statistically significant as well as clinically relevant reductions in breathlessness severity. Verberkt and colleagues72 explored respiratory adverse effects of opioids, a frequently mentioned physician-endorsed barrier towards opioid prescription. After exploring 67 studies, no evidence was found of significant or clinically relevant respiratory adverse effects of short-term use of opioids for chronic breathlessness.…”
Section: Palliative Respiratory Care In Copdmentioning
confidence: 99%